4.4 Å Resolution Cryo-EM structure of human mTOR Complex 1. Issue 12 (1st December 2016) - Yang, Huirong; Wang, Jia; Liu, Mengjie; Chen, Xizi; Huang, Min; Tan, Dan; Dong, Meng-Qiu; Wong, Catherine C L; Wang, Jiawei; Xu, Yanhui; Wang, Hong-Wei
Abstract: Mechanistic target of rapamycin (mTOR) complex 1 (mTORC1) integrates signals from growth factors, cellular energy levels, stress and amino acids to control cell growth and proliferation through regulating translation, autophagy and metabolism. Here we determined the cryo-electron microscopy structure of human mTORC1 at 4.4 Å resolution. The mTORC1 comprises a dimer of heterotrimer (mTOR-Raptor-mLST8) mediated by the mTOR protein. The complex adopts a hollow rhomboid shape with 2-fold symmetry. Notably, mTORC1 shows intrinsic conformational dynamics. Within the complex, the conserved N-terminal caspase-like domain of Raptor faces toward the catalytic cavity of the kinase domain of mTOR. Raptor shows no caspase activity and therefore may bind to TOS motif for substrate recognition. Structural analysis indicates that FKBP12-Rapamycin may generate steric hindrance for substrate entry to the catalytic cavity of mTORC1. The structure provides a basis to understand the assembly of mTORC1 and a framework to characterize the regulatory mechanism of mTORC1 pathway.